The effect of ingestion of red dragon fruit extract on levels of malondialdehyde and superoxide dismutase after strenuous exercise in rats (Rattus norvegicus) [version 3; peer review: 2 approved] - Gusbakti Rusip; Syafrudin Ilyas; Chrismis N. Ginting; I. Nyoman Ehrich Lister; Indra Mukti (F1000Research, 2022)
Background: Prolonged activation of skeletal muscles causes a decrease in the production of fatigue. Exercise with strenuous intensity causes an increase in Reactive Oxygen Species (ROS). An increase in free radicals causes oxidative stress resulting in damage to cell function to mitochondrial dysfunction, and fatigue. This study aimed to determine the antioxidant potential of red dragon fruit (RDF) to delay fatigue due to oxidative stress, which improves cell function in mitochondria. Methods: 25 male rats (Rattus norvegicus) aged three months were divided into five groups: Group K1 was N.A. (No Activity) but drinking and eating; Group K2 performed strenuous exercise without RDF treatment; Groups 3, 4, and 5 (P1, P2 and P3, respectively) performed strenuous exercise and were treated with 75 mg kg-1.bw, 150 mg kg-1.bw, and 300 mg kg-1.bw of RDF extract, respectively. The exercise for the rats involved intense swimming for 20 minutes  a day three time a week for fouweeks.  Malondialdehyde (MDA) dan SOD was measured with the ELISA and histopathology for muscle soleus and lung tissue. Results: Strenuous exercise followed by RDF extract ingestion was compared for fatigue in terms of duration and time; before (24.55±1.38 minute) and after (95.31±7.82 minute) and led to a significant difference of 39% (p<0.01). The study also compared MDA before and after RDF extract ingestion in the K2 vs. the P1 group (p<0.05). At the same time, P2 differed more significantly (p<0.01). This indicated a spread of free radicals and featured histopathological damage of muscle cells. However, ingestion of RDF extract leads to improvement of soleus muscle cells; thus, repairs cell function, delaying fatigue. Conclusion: This study confirmed that strenuous exercise, which causes an increase in ROS, intensifies free radicals with RDF extract ingestion and declines oxidative stress, repairing cell function and delaying fatigue.